KONDISI EKONOMI PEDAGANG KAKI LIMA Di JALAN HR. SOEBRANTAS (Makanan dan Minuman) - Nainggolan, Irfan L.F; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted in hr.soebrantas street of Tampan Pekanbaru Riau District with the problem (1) How the economic condition of street food and beverage vendors in jalan HR. Soebrantas? (2) What are the efforts of street food and beverage vendors in meeting the needs of life on the road HR.soebrantas?. The purpose of this research is to find out the economic condition of street food and beverage vendors at night on HR Street. Soebrantas at this time and know what survival efforts are doing street vendors on HR Street. Soebrantas. This research is quantitative research, the subject in this study of food and beverage traders. Researchers took samples with the slovin formula. With a sample of 72 respondents. To collect data researchers used documentation guidelines and questionnaires. The results of this study show traders still look difficult in economic conditions and require a lot of adjustment in survival. Keywords: Street Vendors, Economic Conditions